2023
DOI: 10.1038/s41598-023-33039-9
|View full text |Cite
|
Sign up to set email alerts
|

Time domain double slit interference of electron produced by XUV synchrotron radiation

Abstract: We present a new realization of the time-domain double-slit experiment with photoelectrons, demonstrating that spontaneous radiation from a bunch of relativistic electrons can be used to control the quantum interference of single-particles. The double-slit arrangement is realized by a pair of light wave packets with attosecond-controlled spacing, which is naturally included in the spontaneous radiation from two undulators in series. Photoelectrons emitted from helium atoms are observed in the energy-domain und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…2 (and the Supplementary Movie ) is a consequence of the fact that even a single photon possesses the property of an OV. Here, we would like to mention the contrast with a recent study that similarly observed the buildup of photoelectron interference using the same undulator 24 . In this study, vortex photons generated by a single undulator were observed to be spatially self-interfering with the double slits.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…2 (and the Supplementary Movie ) is a consequence of the fact that even a single photon possesses the property of an OV. Here, we would like to mention the contrast with a recent study that similarly observed the buildup of photoelectron interference using the same undulator 24 . In this study, vortex photons generated by a single undulator were observed to be spatially self-interfering with the double slits.…”
Section: Resultsmentioning
confidence: 72%
“…In this study, vortex photons generated by a single undulator were observed to be spatially self-interfering with the double slits. On the other hand, in reference 24 , a pair of light wave packets generated by two tandem undulators ionize He atoms, and a resulting pair of photoelectron wave packets interfere with each other in time, which is observed as interference in the energy-domain.…”
Section: Resultsmentioning
confidence: 99%
“…The temporal analog of a double-slit experiment for light waves has also been observed 42 , showing a clear signature of spectral oscillations for time-diffracted light and an inversely proportional relation between slit separation and period of oscillations. For experiments with matter wave packets, the same type of effect was observed, demonstrating a one-by-one detection scheme, allowing us to visualize the buildup of the quantum interference pattern of single-photoelectrons which stochastically arrive at the detector plane 43 .…”
Section: Introductionmentioning
confidence: 62%
“…Moreover, our approach to investigating this experiment can be applied to a wide range of phenomena, and it seems that the predicted non-local temporal interference and associated complementary relationship are universal behaviors of entangled quantum systems that may manifest in various phenomena.In quantum theory, several effects that were initially observed in the spatial domain have subsequently been observed in the time domain. These effects include a wide range of phenomena such as diffraction in time [1][2][3][4] , interference in time [5][6][7][8] , Anderson localization in time 9,10 and several others [11][12][13][14][15] . To extend this line of research, we propose a simple experimental setup that can be used to observe a non-local interference in arrival time, which is analogous to the non-local interference in arrival position observed in entangled particle systems [16][17][18][19][20][21][22][23][24] .The proposed experimental setup involves a double-double-slit arrangement in which a source emits pairs of entangled atoms toward slits 19,25 .…”
mentioning
confidence: 99%
“…In quantum theory, several effects that were initially observed in the spatial domain have subsequently been observed in the time domain. These effects include a wide range of phenomena such as diffraction in time [1][2][3][4] , interference in time [5][6][7][8] , Anderson localization in time 9,10 and several others [11][12][13][14][15] . To extend this line of research, we propose a simple experimental setup that can be used to observe a non-local interference in arrival time, which is analogous to the non-local interference in arrival position observed in entangled particle systems [16][17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%

Non-local temporal interference

Ayatollah Rafsanjani,
Kazemi,
Hosseinzadeh
et al. 2024
Sci Rep